To nie jest fajka. Alienacja znaczenia jako przykład ideologii językowej - Jahns, Michał (Investigationes Linguisticae, 2010)
This article has two main goals. Firstly, to present the basic notions of the theory of language ideologies. Secondly, to discuss the concept of alienation of meaning, which is an example of language ideology. Alienation of meaning is analysed both in terms of “popular” beliefs about the language and as an element of linguistic theory. In order to show a broader perspective of the subject, an interpretation of a work of art is presented. The article ends with a discussion of the utility of the notion of alienation of meaning.